Investigation of Bi2Te3-Bi2Te3-xSx structures by photovoltage measurements - Lošťák, Petr; Drašar, Čestmír; Toušek, Jiří; Prokeš, Jan (Univerzita Pardubice, 2002)
The single-crystal structure of Bi2Te3 -Bi2Te3-xSx with a p-n junction was prepared by the heat treatment of p -Bi2Te3 in sulphur vapors.This structure was characterized by the measurement of the photovoltaic effect. The dependence of the photovoltage at 77 K on the wavelenght shows two speaks at 2.8 um (=0.44 eV) and at 1.9 um (=0.65 eV). The higher peak at 2.8 um (=0.44 eV) corresponds to the bandgap (Eg = 0.43 eV) of Bi8Te7S5. It is created probably by the electric field on the p-n junction at the interface of n -Bi8Te7S5 and deeper lying p -Bi2Te3-xSx with x0.15.
Keywords: směsné telluridy; struktura; fotonapětí; Měření; Detekce